Pemecahan Saham PT MNC Sektor Multimedia: Peluang Emas atau Resiko? - Yuliana Putri; Herlinda Maya Kumala Sari; Ika Oktaviyanti (Faculty of Economics and Business, University of Pancasakti Tegal, 2025)
This study aims to analyze the influence of corporate actions, namely stock split-up, stock split-down, and right issue on the share price of multimedia companies listed on the Indonesia Stock Exchange during the 2019-2024 period. The methods used were descriptive statistical analysis and the Wilcoxon Signed Rank Test test to test the significance of the difference in stock prices before and after corporate action. The data analyzed is secondary data from the company's financial statements and official capital market sources, which are processed using the EViews 12 software. The results show that stock split-ups and right issues do not have a significant influence on stock prices, while stock split-down tends to reduce stock prices insignificantly. The implications of these findings suggest that the market tends to view these corporate actions as nominal changes with no fundamental basis that affect the perception of a company's value. This research makes a new contribution to the understanding of market responses to corporate actions in the multimedia industry in Indonesia, although limited to a quantitative perspective and a specific time period.